2020
DOI: 10.3390/ijerph17186822
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and Impact of a Parent-Child Intervention on Dietary Intake and Physical Activity Behaviours, Parental Motivation, and Parental Body Composition: A Randomized Controlled Trial

Abstract: Adults and children in Canada are not meeting physical activity guidelines nor consuming sufficient nutrient-rich foods. High engagement in these unhealthy behaviours can lead to obesity and its associated diseases. Parent-child interventions aimed at obesity prevention/treatment have assisted families with making positive changes to their nutrition and physical activity behaviours. Given that the home environment shapes early health behaviours, it is important to target both parents and children when addressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 52 publications
4
18
0
1
Order By: Relevance
“…Similar results were also determined that parents' verbal encouragement motivated their children to participate in physical activities [8]. Parental support and interaction with children seem to be important factors for children's development of habits of regular physical activity behaviours [9][10][11][12] and it is interesting to see that such influences are closely related to the social and economic background of the parents [13][14][15].…”
Section: Introductionsupporting
confidence: 53%
“…Similar results were also determined that parents' verbal encouragement motivated their children to participate in physical activities [8]. Parental support and interaction with children seem to be important factors for children's development of habits of regular physical activity behaviours [9][10][11][12] and it is interesting to see that such influences are closely related to the social and economic background of the parents [13][14][15].…”
Section: Introductionsupporting
confidence: 53%
“…Two studies have exclusively targeted parents with overweight or obesity and measured both parent and child dietary outcomes. One study included a 3-month telephone coaching intervention for parents of children ages 2–10 ( 35 ) and did not produce changes in any parent or child dietary components. The other, a 6-month individual- and group-based counseling weight management program for parents of children age 7–18, measured fruit and vegetable intake at all time points, but resulted in no changes in parent or child intake ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…Information and communication technologies vs. traditional approaches targeting parents to improve healthy diet or body mass index in preschoolers: a systematic review General characteristics and risk of bias of included studies are represented in Table 1 [20][21][22][23][24][25][26][27] . Two had a not defined setting by the nature of the intervention (ICT-T exclusively).…”
Section: Resultsmentioning
confidence: 99%
“…In Table 2 [20][21][22][23][24][25][26][27] is reported effectiveness of the interventions. For CHD, the only study with negative effects reported that intake of fruits and vegetables (FV) and unsweetened beverages per day was more pronounced for children in the CG at baseline and follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation